Strain selection for improvement of Bradyrhizobium japonicum competitiveness for nodulation of soybean - Althabegoiti, María Julia (2008)
A Bradyrhizobium japonicum USDA 110-derived strain able to produce wider halos in soft-agar medium than its parental strain was obtained by recurrent selection. It was more chemotactic than the wild type towards mannitol and three amino acids. When cultured in minimal medium with mannitol as a single carbon-source, it had one thick subpolar flagellum as the wild type, plus several other flagella that were thinner and sinusoidal. Root adsorption and infectivity in liquid media were 50-100% higher for the selected strain, but root colonization in water-unsaturated vermiculite was similar to the wild type. A field experiment was then carried out in a soil with a naturalized population of 1.8 × 105 soybean-nodulating rhizobia g of soil -1. Bradyrhizobium japonicum strains were inoculated either on the soybean seeds or in the sowing furrows. Nodule occupation was doubled when the strains were inoculated in the sowing furrows with respect to seed inoculation (significant with P<0.05). On comparing strains, nodule occupation with seed inoculation was 6% or 10% for the wild type or selected strains, respectively, without a statistically significant difference, while when inoculated in the sowing furrows, nodule occupation increased to 12% and 22%, respectively (differences significant with P<0.05).